Maritime cadet experiences with bridge simulators in terrestrial navigation education - Sibali, Alwi; Kurniawaty, Kurniawaty; Amran, Amran; Misnawati, Misnawati (Frontiers in Education, 2026)
Bridge simulators are increasingly central to maritime education, particularly for developing skills in terrestrial navigation. However, research often prioritizes technical fidelity over the learner’s perspective. Adopting a qualitative descriptive methodological approach, this study explores how 30 final-year cadets at Politeknik Maritim AMI Makassar experience and interpret the use of bridge simulators. Data were triangulated from semi-structured interviews, direct observation, and document analysis. The findings reveal four consolidated themes: (1) Visual Realism and Situated Cognition; (2) Bridging Theory and Practice through Transfer of Learning; (3) Psycho-Social Dynamics; and (4) Instructional Scaffolding and Design Constraints. While the simulator effectively bridged the gap between abstract theory and practice for many, significant challenges emerged regarding cognitive overload, “transfer gaps” under pressure, and anxiety within the socio-technical environment. The study’s originality lies in unpacking the specific psycho-social barriers in Eastern Indonesian maritime education, offering novel insights beyond typical technical evaluations. The article concludes with actionable policy recommendations for curriculum integration and instructor training to optimize simulator pedagogy in developing maritime nations.